RANCANGAN APLIKASI E-SCHED UNTUK SEKOLAH PILOT SEBAGAI UPAYA PEMERATAAN TRAFFIC DI BANDAR UDARA BUDIARTO CURUG - Danu Fadel Laksana; Julfansyah Margolang; Meita Maharani Sukma (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Budiarto airport is a training airport that located at tangerang curug. Provide service three aviation school, budiarto airport give service for about 200 in a day. Budiarto airport serve 5 type of training flight include circuit training, instrument training, area training, night flight training, and cross country training. Beside provide service for training flight budiarto airport also provide service for Balai Kalibrasi Fasilitas Penerbangan. As an airport that gives service for 3 aviation school traffic accumulation become normal situation in Budiarto airport. Lack of coordination between 3 aviation school and the Regulation of training flight request become the main factor of traffic accumulation. Sometimes there are 2 instrument training request in one session, as a result one of them must wait other plane to finish the training, because the capacity for instrument training just available for 1 aircraft. Massive development a technology create innovations that help human in daily live. In aviation using technology in need reduce workload for personnel. But some application is difficult to operate. This case make the writer to design some application that can be operate easily and overcome some traffic issues at Budiarto. Hopefully the design of this application can be realize and can be use for all training airport in Indonesia. This application designed base on writers experience in On The Job Training in Budiarto airport.